Understanding The Human Rights Discrimination of South Korea Muslims - Sakinah, Nur; Kurniawati, Erna (Jurnal Paradigma, 2024)
This research analyzes discrimination against Muslims in South Korea, a country known to be advanced in terms of technology and economy. Various factors influence this discrimination, including anti-Islam propaganda, lack of understanding about Islam, and incidents of religious-based terrorism in the world. In the last few years, namely 2018-2023, human rights discrimination against the Muslim community in South Korea has become a public concern. In South Korea, discrimination against Muslims leads to human rights violations and hatred. The complexity of this problem is further strengthened by the interaction of various factors, social changes, and the dynamics of life in South Korea. This research uses a qualitative approach and case studies to understand this phenomenon from the perspective of perpetrators and victims of discrimination, involving local South Korean residents and Muslims living in South Korea. The results of the research show that there is a significant influence from various parties which influences the occurrence of direct and indirect acts of human rights discrimination against Muslims in South Korea, impacting the human rights of Muslims living in South Korea. Keywords : Discrimination, Muslims in South Korea, Human Rights.